Analytical solution of quasi-equilibrium problems in one variable - Navarro R., Frank (2020)
The quasi-equilibrium problem (QEP) is a generalization of the classic equilibrium problem (EP) where the constraint set does depend on the reference point. It generalizes important problems such as quasivariational inequalities (QVI) and generalized Nash equilibrium problems (GNEP). In recent years the study of QEP has increased, both from the point of view of existence and uniqueness of solutions and of algorithms to find solutions. In both types of research, assumptions and theoretical results are given, so it is necessary to be able to show examples that can show the validity or falsity of those results . This article aims to help in this task, providing two results to find the whole solution set of QEPs in a variable.